Prevalence of preterm birth and associated factors among mothers who gave birth in public hospitals of east Gojjam zone, Ethiopia - Tafere Birlie Ayele; Yikeber Abebaw Moyehodie (BMC Pregnancy and Childbirth, 2023)
Abstract Backgrounds Preterm birth is defined as babies born alive before 37 weeks of pregnancy or fewer than 259 days since the first day of a woman’s last menstrual period. Globally, 14.84 million babies were preterm births. Preterm infants are at risk for specific diseases related to the immaturity of various organ systems. This study aimed to assess the prevalence of preterm birth and associated factors among mothers who gave birth in public hospitals of east Gojjam zone, Ethiopia. Methods An institutional-based cross-sectional study was conducted from April 1 up to June 30, 2021, in public hospitals in the east Gojjam zone. Systematic random sampling was used. Data were collected through structured questionnaires, patient interviews and patient card reviews. We used binary logistic regression analysis with 95% CI and P-value < 0.05 to identify the significant factors with preterm birth. Results Out of 615 mothers, 13.2% gave a preterm birth. Antenatal care (AOR = 2.87; 95% CI = (1.67, 5.09)), educational status of mother (AOR = 2.79; 95% CI = (1.27, 6.67)), husband educational status(AOR = 2.11; 95% CI = (1.10, 4.18)), Average monthly family income(AOR = 1.95; 95% CI = (1.05, 3.75)),family size(AOR = 0.15; 95% CI = (0.03, 0.67)), multifetal gestation (AOR = 3.30; 95% CI = (1.29, 8.69), having Premature Rupture Of Membrane (AOR = 6.46; 95% CI= (2.52, 18.24)), history of chronic illness (AOR = 3.94; 95% CI = (1.67, 9.45)), being HIV positive(AOR = 6.99; 95% CI= (1.13, 44.65)), Ante-Partum Hemorrhage (AOR = 3.62; 95% CI= (1.12, 12.59)), pregnancy Induced Hypertension (AOR = 3.61; 95% CI= (1.19, 11.84)), mode of delivery (AOR = 7.16; 95% CI = (2.09, 29.29)), and onset of labor (AOR = 0.10; 95% CI = (0.03, 0.29)) were found to be significantly associated with preterm birth. Conclusions antenatal care, educational status of the mother, husband’s educational status, family income, family size, multifetal gestation, Premature Rupture of the membrane, history of chronic illness, being HIV positive, Ante-Partum Hemorrhage, pregnancy Induced Hypertension, mode of delivery, and the onset of labor were found to be significantly associated with preterm birth. To minimize the proportion of preterm birth focusing on this important variables, timely identification of obstetric complications, strengthening early screening of HIV and high-risk pregnancies like multiple gestations, PIH and APH were important.